Peningkatan Ketahanan Pangan di Desa Pungka Kecamatan Unter Iwes Kabupaten Sumbawa - Ahmad Yani; Mariyam Al Haddar; Diana Anggraeni; Muhammad Aditya Warman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Pungka Village is one of 8 villages and sub-districts located in Unter Iwes District, Sumbawa Besar Regency, West Nusa Tenggara Province. Pungka Village is located between Perate Village and Kerekeh Village. Most of the tribes who live in Pungka Village come from the Sumbawa tribe. This village has a population of 1963 people, consisting of 973 men, 990 women, with a total of 544 heads of families and most of them are ethnic Sumbawa. The livelihoods of the people of Pungka Village are farmers and breeders. Some of the programs implemented include teaching residents how to use their front yards to be managed properly so as to strengthen community food security while increasing family income. The second program carried out is the healthy protein movement for students to provide high protein products such as eggs and milk with the aim of helping the community to keep the immune system good and strong, so that people are not susceptible to Covid-19 and other diseases. The next program is training on making fermented feed processing technology from agricultural waste, community education programs about new normal and clean and healthy living habits, mask movement programs and finally a program to monitor the nutritional status of toddlers through posyandu activities. The programs are carried out directly or in the field, to residents' homes in order to educate them while still applying health protocols. Keywords: Pungka Village, family yard, healthy protein, and community education